A study of selected financial implications of the federal "No Child Left Behind" (P.L. #107-110) law on Kansas public school districts - Gerber, Dennis L. (Kansas State University, 2007)
The purpose of this study was to examine selected financial implications of various mandates in the No Child Left Behind Act (P.L. #107-110 popularly known as NCLB) of 2001 on Kansas public school districts. Specific mandates included accountability for student achievement, more educational choices for parents, teaching methods that produce results, emphasis on reading, emphasis on math, hiring highly qualified teachers, and teaching English to all students. Expenditures for these mandates were identified and analyzed to estimate which mandates were perceived as having the greatest financial impact on Kansas school districts’ budgets during FY 2006—the fiscal year of record for this study. A survey research design was utilized for this study. The survey instrument sought opinions about expenditure items categorized according to the selected mandates. A seven-point one-directional intensity scale was used to determine school superintendents’ attitudes toward the financial impact of selected mandates on their school districts’ budget. Data were analyzed and reported using measures of central tendency, range, inter-quartile analysis, and standard deviation. Narrative responses from respondents were also presented. Analysis of data revealed that many Kansas public schools are presently experiencing economic and political conditions that could interfere with the state’s ability to provide a quality education for all students under NCLB. Such conditions often include: (1) decreasing student enrollment, resulting in consolidation of some school districts; (2) difficulty hiring and retaining highly qualified teachers and administrators: (3) increasing numbers of superintendents with less experience in a position that has become more demanding and complex; (4) increased need to use existing funds to improve the academic performance of economically disadvantaged and special education students; and (5) having to rely on the singular standard of annual assessment of student performance in math and reading to determine accreditation success or failure.
Keywords: school finance; no child left behind; Education, Finance (0277)